2019
DOI: 10.7759/cureus.4430
|View full text |Cite
|
Sign up to set email alerts
|

Eagle’s Syndrome: A Case Report of a Unilateral Elongated Styloid Process

Abstract: When styloid process elongation or stylohyoid ligament calcification can lead to various symptoms, such as dysphagia, facial pain, globus sensation, and headache, it is termed Eagle’s syndrome. It may be unilateral or bilateral. Though the overall prevalence in adults is 4%, only 0.16% of patients are symptomatic. Since the symptoms mimic several other orofacial pains and neuralgia, the diagnosis must be made through a detailed history, clinical examination, and various imaging modalities. The case of facial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
0
7
0
4
Order By: Relevance
“…Eagle's syndrome is more commonly seen in females. 5 Eagle's syndrome refers to a constellation of neuropathic and vascular occlusive symptoms caused by pathologic elongation or angulation of the styloid process and styloid chain, clinically characterized by throat and neck pain, radiating into the ear. 6 In most of the individuals, the normal length of the styloid process ranges between 20mm to 30 mm; when it exceeds 30mm, it is considered as elongated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eagle's syndrome is more commonly seen in females. 5 Eagle's syndrome refers to a constellation of neuropathic and vascular occlusive symptoms caused by pathologic elongation or angulation of the styloid process and styloid chain, clinically characterized by throat and neck pain, radiating into the ear. 6 In most of the individuals, the normal length of the styloid process ranges between 20mm to 30 mm; when it exceeds 30mm, it is considered as elongated.…”
Section: Discussionmentioning
confidence: 99%
“…6 In most of the individuals, the normal length of the styloid process ranges between 20mm to 30 mm; when it exceeds 30mm, it is considered as elongated. 5 Panwar et al (2022) reported a case of Eagle's syndrome in a 47-year-old woman with symptomatic bilateral elongation of the styloid process. The lengths of the right and left styloid processes were 60.5mm and 70.74mm,respectively, which is one of the longest ever reported.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of Eagle's syndrome is based on symptomatology; digital palpation of the styloid process in the tonsillar fossa; radiographical evidence of calcification or elongation of the styloid process on x-ray or computed tomography of the neck; or a positive local anaesthetic infiltration test, whereby symptoms are relieved following injection into the anterior tonsillar pillar. 23 Treatment of Eagle's syndrome may be conservative or surgical. Conservative management involves injecting steroids into the lesser cornu of the hyoid or the inferior aspect of the tonsillar fossa.…”
Section: Diagnosismentioning
confidence: 99%
“…Eagle syndrome represents a constellation of symptoms, primarily facial pain, believed to be related to a prolongation of the styloid process or calcification of the stylohyoid and stylomandibular ligament [ 1 , 2 ]. It is a rare entity that is not commonly suspected in clinical practice [ 3 ]. The reported incidence of an elongated styloid process, defined as greater than 25 mm, ranges from 1-7% of the population, but only 4-7% of these patients experience related symptoms [ 1 , 4 ].…”
mentioning
confidence: 99%